Reconstructing a Deuteronomistic Athaliah in the (South) African context: A critique of the patriarchal perception of women - Mtshiselwa, Ndikhokele (Verbum et ecclesia, 2015)
Angie Motshekga, the president of the Women's League of the ruling African National Congress (ANC 2014), is reported to have said that South Africa is not ready to have a female president ...' What is perturbing about her statement is the presupposition that South-African society perceives women as presently incapable of leading the country as president. Given the variety of literature on female empowerment in South Africa, Motshekga's statement comes both as a disappointment and a disempowering assertion as it does not exhibit a clear attempt to address patriarchy. This article re-interprets the character of Athaliah in 2 Kings 11 and probes it for the empowering possibility that it offers the women of South Africa. It argues that Athaliah was a politically astute queen and that the scarcity of female rulers in ancient Israel confirms the patriarchal bias against women. Thus, drawing from the reconstructed character of Athaliah and from the leadership demonstrated by selected women politicians against a patriarchal paradigm that is part of African cultures, the article submits that the perception of women as capable of leading South Africa as president is justified.Intradisciplinary and/or interdisciplinary implications: The present article partly responds to Angie Motshekga's statement that South Africa is not ready to have a female president ...' Thus, drawing from the insight in the fields of the Old Testament, social sciences and gender studies, this article submits that the perception that women are capable of leading South Africa as president is warranted.